PENGARUH LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK DISKUSI TERHADAP SISWA YANG MENGALAMI KEJENUHAN BELAJAR DI KELAS - Riska Yolanda (PUSKAPAD, 2025)
This study aims to analyze students who experience learning saturation before and after being given services and whether there is an influence of group guidance with discussion techniques on students who experience learning saturation in class VIII MTS Al-Washliyah Bangun Purba. This type of research is quantitative pre-experiment with One Group Pre-test Post-test Design method. The population of this study was 36 students in class VIII MTS, sampling with purposive sampling method of 10 students. The data of this study were collected using an instrument or questionnaire of learning saturation with a Likert scale, statement items totaling 37 items that have been valid and reliable then the data were analyzed using the Wilcoxon test. The resulting data shows that students experience learning saturation in class VIII MTS Al-Washliyah Bangun Purba before and after being given group guidance with discussion techniques. From the data analysis, Asymp.Sig.(2-tailed) is obtained with a value of 0.000. Because 0.000 is smaller than <0.05, Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a difference in students who experience learning saturation before and after being given group guidance services with effective discussion techniques to reduce students who experience learning saturation.